2019
DOI: 10.11152/mu-2002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of ultrasound and contrast-enhanced ultrasound in primary hepatic carcinosarcoma: three cases report

Abstract: Primary hepatic carcinosarcoma (PHCS) is a very rare malignant tumor with a poor prognosis. Previous studies in the English-language literature were case reports, focused on the clinical aspects, pathology and pathogenesis. Much is unknownabout the imaging characteristics of PHCS while ultrasound is the first imaging examination for hepatic disease. Contrastenhancedultrasound (CEUS) is a proven method that improves the detection and characterization of focal liver lesions. The purpose of the paper is to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Contrast-enhanced ultrasound detects a thicker ring-enhancing part of the abscess than that of PLSC patients, 39 peripheral nodular enhancement of PLSC, and hypervascularization of HCC in the arterial phase. 31 , 40 However, these differences are minor and difficult to practice, so difficulties in diagnoses should always be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced ultrasound detects a thicker ring-enhancing part of the abscess than that of PLSC patients, 39 peripheral nodular enhancement of PLSC, and hypervascularization of HCC in the arterial phase. 31 , 40 However, these differences are minor and difficult to practice, so difficulties in diagnoses should always be considered.…”
Section: Discussionmentioning
confidence: 99%
“…For patients suffering from advanced PLSC at initial diagnosis and with recurrence after surgery, the prognosis is worse, with a median OS of less than 6 months. 43 Cytotoxicity drugs and sorafenib 44,45 have been used for treatments, including gemcitabine combined with paclitaxel, 35 gemcitabine combined with cisplatin, 40 and pirarubicin combined with cisplatin, 46 but only in case reports. Epirubicin combined with cisplatin (Case 4) and docetaxel combined with cisplatin (Case 9) have been used in two of our cases, but unplanned terminations made it impossible to provide information about the treatment-related prognoses.…”
Section: Dovepressmentioning
confidence: 99%
“…The prognosis of HCS cases is often worse than that of conventional liver neoplasms, which may be attributed to the aggressive sarcomatous elements with their extensive differentiation [11] . A study from Japan analyzed 21 reported cases of primary HCS and found that the survival time of patients who received surgery and postoperative comprehensive treatment was signi cantly longer than that of patients who did not undergo surgery, with a survival time for the former group of up to 30 months [12,13] . Surgical resection appears to be the most effective treatment for HCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the retrospective literature, 24 articles 2,3,[7][8][9][10][11]13,14,17,[19][20][21][22][23][24][26][27][28][29][30][31][32][33] were involved in the imaging manifestations, including our study of total of 35 patients. Due to the different proportion of carcinomatous components and sarcomatous components in HCS, and their pathological types were not the same, the imaging manifestations were different.…”
Section: Discussionmentioning
confidence: 99%